Communication Strategy for the Interaction of Local Governments and the Public in Addressing Municipal Waste Management - Levchenko, Nataliia; Datsii, Nadiia; Rodchenko, Ihor (University Scientific Notes, 2019)
The article states that overload landfills have become a big environmental threat to the environment and public life, the extent of which is steadily increasing provided, that the principle of «extended producer responsibility» in Ukraine do not work. It is stressed that the administrative-territorial reform and the whole burden of the management of municipal waste are vested in the local authorities. The necessity of intensifying the dialogue of local authorities and the public on the treatment of municipal waste is stressed. It is established that a long time communicative interaction between public authorities and the public on these issues be limited solely to inquiries and complaints. Accentuated that at present the public needs a better communication vehicle for engagement with local authorities, which would reverse the information when provided to a positive communicative effect and contributed to the transformation of information into a decision, and decisions on action. It is proved that the solution of this issue possible in the development of the communicative strategy of interaction of local governments and the public, able to ensure sustainable development of territories thanks to improve the condition of landfills and dumps, the organization of separate waste collection and recycling. The proposed etiology develop a communication strategy of interaction of local governments and the public in addressing issues of treatment of municipal waste, taking into account its compatibility with other concepts, strategies and development plans of the territories. In detail each of the stages of development of the communication strategy of interaction of local governments and the public. It is proved that the introduction in practice of the proposed topolog develop a communication strategy of interaction of local governments and the public in addressing issues of treatment of municipal waste will simplify the development process and provide clarity to determine the most appropriate channels of communication with each of the priority stakeholder groups interested in the growth of the percentage of coverage, the provision of municipal solid waste management, improvement of landfills and dumps, which have become a threat to the environment and public life.
Keywords: strategy; communication strategy; local government and public interaction strategy; municipal waste